INFORMATION AND COMMUNICATION TECHNOLOGIES-AS A TOOL FOR QUALITY DISTANCE EDUCATION - Morze, H.B.; Glazunova О.Г. (Journal of Information Technologies in Education (ITE), 2010)
The article is devoted to enhancing the quality of organizational and methodological support in the learning process of students by correspondence through the use of modern information and communication technologies and distance learning.